Adaptable Three Dimensional System for Building Inspection Management - Abou Shaar, Belal (University of Waterloo, 2012)
Sustaining the safety and operability of civil infrastructure assets, including buildings, is a complex undertaking that requires a perpetual cycle involving inspection, and further decisions for renewal fund allocation. However, inspection, which is the basis for all subsequent decisions, is a complex task to manage, particularly when a large number of assets are involved. The current lack of a structured process with visual referencing as well as the high subjectivity and inflexibility to changing inspection requirements make current inspections very costly and time consuming. This research improves the building inspection process by introducing a 3D system for inspection management that has four unique features: (1) a structured assessment approach that considers multiple organizations, buildings and inspectors, using a GIS interface; (2) a 3D visual referencing method for marking problem areas during inspections to facilitate all on-site inspections, thus reducing time and cost; (3) a visual guidance module to reduce inspection subjectivity; and (4) a flexible module for designing different assessment types. The proposed inspection management system creates 3D building plans from 2D Computer-Aided Drawing (CAD) to provide location referencing that enhances inspection effectiveness. The visual guidance system allows inspectors with various experience levels to perform consistent inspections and requires less training, thus reducing costs. Flexible inspection generation also allows a variety of inspection types, such as condition and level of service, to be readily incorporated. A computerized prototype system has been developed using the Windows Presentation Foundation’s XAML markup language with underlying C# programming on a tablet computer for experimentation. The thesis provides a detailed description of system development and reports the benefits of the system on a sample inspection. Accordingly, the system has proven most useful for large organizations that own a large number of building assets that require frequent inspections.
Keywords: inspection management system; building inspection; 3D inspection; visual inspection; building ims; 3d building inspection; Civil Engineering